411 LEARNING CURVES IN MINIMALLY INVASIVE ESOPHAGECTOMY: A SYSTEMATIC REVIEW. (14th September 2020) - Prasad, P; Wallace, L; Navidi, M; Wahed, S; Immanuel, A; Phillips, A
Abstract:  : Minimally invasive techniques are being increasingly used in the treatment of esophageal cancer. The learning curve for minimally invasive esophagectomy (MIE) is variable and can have an impact upon training delivered within residency and fellowship programmes. The aims of this review are to critically appraise current literature on the learning curve for MIE, identify what parameter(s) is used to quantify achieving competence and determine if there is evidence of resultant impact on surgical training. Methods: A search of the major reference databases (MEDLINE, EMBASE, Cochrane) was performed with no time limits up to the date of the search (February 2020). Results were screened in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and study quality assessed using the Newcastle-Ottawa Scale for cohort studies. Results: Twenty-one studies comprising 2720 patients were included- 17 studies reported on a combination of thoracoscopic, hybrid and total MIE, 3 studies reported robotic assisted alone and 1 study evaluated robotic assisted and thoracoscopic esophagectomy. 3 studies used a cumulative sum (CUSUM) analysis to define learning, 1 study used CUSUM and another parameter and 17 studies used one or more parameters. Quantification of surgical competence was variable and ranged from 12–80 cases for robotic surgery and 12–60 cases for other modes of MIE. One study reported trainees achieving MIE skills quicker if mentoring surgeons had attained proficiency on the learning curve. Conclusion: Learning curves in MIE remain ill-defined with limited evidence on impact upon training received by residents and fellows. Additionally, the parameters used to define achievement of surgical competency is heterogenous. As minimally invasive techniques are increasingly adopted, specific standards to help define competence need to be identified and agreed on. This could help in designing training programmes and improve the rate of achieving competency.